The Odor Value Approach to Aroma Contribution Analysis and Aroma Mapping: A Systematic Review - Salma Aulia Zahra; Asep Kadarohman (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2026)
Aroma is a complex matrix consisting hundreds of volatile compounds, so there are challenges in understanding aroma characteristics and their mapping. There is an approach called odor value that connects chemical information with sensory perception and provides a visual tool for aroma mapping. However, literature studies of Odor Value are rare. This study aims to review the principle of odor value in aroma contribution analysis and how it can be integrated with the Perfumery Ternary Diagram for aroma mapping. The article selection method used the PRISMA guideline with the keywords odor value and aroma analysis published from 2005-2025 in the ScienceDirect database and obtained 10 articles that met the criteria. This method can provide initial understanding and map the scope of the available literature. From the review results, it is known that odor value is influenced by the concentration of compounds in the headspace, aroma threshold values, activity coefficients, and molecular interactions. In addition, the integration of odor value into the Perfume Ternary Diagram plays a direct role in determining the aroma mapping pattern so that it can provide information about aroma dominance, component diffusion in the matrix, and the influence of solvents in the matrix.Keywords: Odor Value, Perfumery Ternary Diagram, Aroma Analysis, Aroma Contribution, Aroma Mapping